2017
DOI: 10.18632/oncotarget.18449
|View full text |Cite
|
Sign up to set email alerts
|

Secreted miR-210-3p as non-invasive biomarker in clear cell renal cell carcinoma

Abstract: The most common subtype of renal cell carcinoma (RCC) is clear cell RCC (ccRCC). It accounts for 70-80% of all renal malignancies representing the third most common urological cancer after prostate and bladder cancer. The identification of non-invasive biomarkers for the diagnosis and responsiveness to therapy of ccRCC may represent a relevant step-forward in ccRCC management. The aim of this study is to evaluate whether specific miRNAs deregulated in ccRCC tissues present altered levels also in urine specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…Thus, among molecules in exosomes, miRNAs have been investigated due to their regulatory role in gene expression [ 26 ]. Some reports have shown that oncogenic miRNA are associated with prognosis or as useful biomarkers in ccRCC [ 20 , 27 , 28 ]. Among oncogenic miRNAs, miR-224 is upregulated and plays an oncogenic function in hepatocellular carcinoma [ 27 , 29 , 30 ], esophageal squamous cell carcinoma [ 31 ], colorectal cancer [ 32 , 33 ], and non-small cell lung cancer [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, among molecules in exosomes, miRNAs have been investigated due to their regulatory role in gene expression [ 26 ]. Some reports have shown that oncogenic miRNA are associated with prognosis or as useful biomarkers in ccRCC [ 20 , 27 , 28 ]. Among oncogenic miRNAs, miR-224 is upregulated and plays an oncogenic function in hepatocellular carcinoma [ 27 , 29 , 30 ], esophageal squamous cell carcinoma [ 31 ], colorectal cancer [ 32 , 33 ], and non-small cell lung cancer [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first to show that exosomal miR-224 levels parallel those of miRNA-224 in ccRCC tissues and are significantly associated with prognosis in ccRCC patients. Interestingly Petrozza et al have reported that miR-210-3p extracted from urinary specimens in surgical treatment is useful as a non-invasive biomarker [ 28 ]. Moreover, expression of miR-210-3p extracted from urinary specimens in surgical treatment was associated with complete surgical resection or response to treatment in ccRCC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, abnormal expression of miR‐210 can impact dramatically on cell behaviour, with a large body of evidence now gathered which links it with cancer development (Bavelloni et al, 2017; Dang & Myers, 2015). For example, overexpression of miR‐210 has been associated with breast (Camps et al, 2008; Li et al, 2013; Madhavan et al, 2012), renal (Petrozza et al, 2017), lung (He et al, 2018), colorectal (Sabry et al, 2018) and pancreatic (Greither et al, 2010) cancers among others. Together, these studies indicate a vital contributory role for miR‐210 in cancer development, as well as demonstrating its potential value as a prognostic cancer marker (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) is the third most common urological malignancy in the USA and represents 2-3% of all adult malignancies. Furthermore, the incidence rate has progressively increased, particularly in young patients and or those with high-grade disease (1)(2)(3). In 2017, ~63,990 cases were diagnosed with kidney and renal pelvis cancer and 14,400 cases were expected to succumb to disease in the USA alone (4).…”
Section: Introductionmentioning
confidence: 99%